Importance of Target Gene Locus on the Stability of Recombinant Viruses in the Baculovirus Expression System - Jong Ho Lee; Dong-Hyun Lee; Hyuk-Jin Moon; Soo Dong Woo (Viruses)
In the baculovirus expression system, recombinant viruses generated via bacmids often exhibit reduced expression and genetic stability of target genes during serial passages. This instability is thought to arise from the proximity of non-essential exogenous genes to the target gene insertion site. This study investigated the impact of the target gene insertion locus on its expression and stability within the recombinant viral genome. In addition to the conventional polyhedrin (polh) locus, we evaluated four additional loci located distal to the non-essential exogenous genes. Among them, the ODV-e56 and ChiA/v-cath loci maintained target gene expression and genetic stability more effectively than the polh and p10 loci, even after ten consecutive undiluted viral passages. Notably, essential or functionally important viral genes were located near the ODV-e56 and ChiA/v-cath loci, whereas such genes were absent near the p10 locus. These findings suggest that enhanced stability and expression are associated with the proximity to essential viral genes. Therefore, the strategic selection of target gene insertion sites in close proximity to essential viral elements, rather than simply avoiding non-essential exogenous regions, represents a promising strategy to enhance recombinant protein production in baculovirus expression systems.